EFFECT OF CHALLENGE-BASED AND ACTIVITY-BASED LEARNING APPROACHES ON TECHNICAL COLLEGE STUDENT’S ACHIEVEMENTS AND RETENTION IN WOODWORK TECHNOLOGY - M, Hassan A; Ogbuanya, T C (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
This study was designed to determine the effects of challenge-based and activity-based learning approaches on technical college students’ achievement and retention in woodwork technology. A pre-test, post-test, non-equivalent control group, a quasi-experimental research design was adopted. The study constituted a total number of 122 subjects, 63 for Challenge-based learning, while 59 for activity-based learning. three research questions and three null hypotheses, tested at 0.05 level of significance, guided the study. The instruments used for data collection were Woodwork Cognitive Achievement Test (WCAT). Other instruments used were the challenge-based and activity-based learning lesson plans. The items of the WCAT were based on a table of specifications built in order to ensure the content validity of the test. The instruments were also subjected to face validation by five experts in woodwork technology from the Department of Industrial and Technology Education, Federal University of Technology Minna and woodwork technology teachers at Government Technical Colleges in Niger State. The WCAT was trial-tested to determine its psychometric indices and reliability coefficient. The trial test for determining the coefficient of stability of the WCAT was carried out using the test re-test reliability method. Pearson product-moment correlation coefficient of WCAT was found to be .78. In addition, Kuder Richardson 21 (K-R 21) was used to test the internal consistency of the WCAT. The reliability coefficient obtained was .76. Mean was used to answer the research questions; while ANCOVA was employed to test the hypotheses. The study revealed that students taught woodwork using the challenge-base learning instructional approach had a higher mean score than students taught using the activity-based learning teaching method in cognitive achievement test. In each mean score of males taught woodwork using a challenge-based learning instructional approach was higher than the mean score of females taught using the same challenge-based learning instructional approach in the cognitive achievement test. Consequently, the research recommended that the National Board for Technical Education (NBTE) should consider a review of the Woodwork work curriculum for Technical Colleges with a view to incorporating the challenge-based learning instructional approach into the teaching of the woodwork.